Quantitative susceptibility mapping (QSM) detects abnormalities in cartilage canals in a goat model of preclinical osteochondritis dissecans (OCD) - Wang, Luning (Magn Reson Med, 2016)
PURPOSE: To use quantitative susceptibility mapping (QSM) to investigate changes in cartilage canals in the distal femur of juvenile goats after their surgical transection. METHODS: Chondronecrosis was surgically induced in the right medial femoral condyles of four 4-day-old goats. Both the operated and control knees were harvested at 2, 3, 5, and 10 weeks after the surgeries. Ex vivo MRI scans were conducted at 9.4T using T(RAFF)-weighted fast spin echo imaging and QSM to detect areas of chondronecrosis and investigate cartilage canal abnormalities. Hematoxylin & eosin (H&E) and safranin O stained histological sections from these same areas were evaluated to assess the affected tissues. RESULTS: Both the histological sections and the T(RAFF)-weighted images of the femoral condyles demonstrated focal areas of chondronecrosis, evidenced by pyknotic chondrocyte nuclei, loss of matrix staining, and altered MR image contrast. At increasing time-points after surgery, progressive changes and eventual disappearance of abnormal cartilage canals were observed in areas of chondronecrosis by using QSM. CONCLUSION: Abnormal cartilage canals were directly visualized in areas of surgically-induced chondronecrosis. QSM enabled investigation of the vascular changes accompanying chondronecrosis in juvenile goats.